Synthesis of 3-aminocoumarin-N-benzylpyridinium conjugates with nanomolar inhibitory activity against acetylcholinesterase - Khunnawutmanotham, Nisachon; Laongthipparos, Cherdchai; Saparpakorn, Patchreenart; Chimnoi, Nitirat; Techasakul, Supanna (Beilstein Journal of Organic Chemistry, 2018)
A series of 3-amino-6,7-dimethoxycoumarins conjugated with the N-benzylpyridinium moiety through an amide-bond linkage was synthesized and evaluated for their acetylcholinesterase inhibitory activity. A number of the benzylpyridinium derivatives exhibited potent activities with inhibitory concentration (IC50) values in the nanomolar concentration range. Among them, the 2,3-difluorobenzylpyridinium-containing compound was the most potent inhibitor with an IC50 value of 1.53 ± 0.01 nM. Docking studies revealed that the synthesized compounds inhibit the target enzyme by a dual binding site mechanism whereby the coumarin portion binds with the peripheral anionic site while the N-benzylpyridinium residue binds with the catalytic anionic site of the enzyme.
Keywords: acetylcholinesterase inhibitor; 3-aminocoumarin; N-benzylpyridinium; dual binding site inhibitor; synthesis

World Population Prospects: The 2017 Revision - United Nations, Department of Economic and Social Affairs, Population Division (United Nations, 2017)

World Alzheimer Report 2016. Improving healthcare for people living with dementia. Coverage, quality and cost now and in the future - Prince, M.; Comas-Herrera, A.; Knapp, M.; Guerchet, M.; Karagiannidou, M. (Alzheimer’s Disease International, 2016)

(untitled) - Inestrosa, N. C.; Alvarez, A.; Pérez, C. A.; Moreno, R. D.; Vicente, M.; Linker, C.; Casanueva, O. I.; Soto, C.; Garrido, J. (Neuron, 1996)

(untitled) - Alvarez, A.; Opazo, C.; Alarcón, R.; Garrido, J.; Inestrosa, N. C. (J. Mol. Biol., 1997)

(untitled) - Gemma, S.; Gabellieri, E.; Huleatt, P.; Fattorusso, C.; Borriello, M.; Catalanotti, B.; Butini, S.; De Angelis, M.; Novellino, E.; Nacci, V.; Belinskaya, T.; Saxena, A.; et al. (J. Med. Chem., 2006)

(untitled) - Camps, P.; Formosa, X.; Galdeano, C.; Gómez, T.; Muñoz-Torrero, D.; Ramírez, L.; Viayna, E.; Gómez, E.; Isambert, N.; Lavilla, R.; Badia, A.; Clos, M. V.; et al. (Chem.-Biol. Interact., 2010)

(untitled) - Alonso, D.; Dorronsoro, I.; Rubio, L.; Muñoz, P.; García-Palomero, E.; Del Monte, M.; Bidon-Chanal, A.; Orozco, M.; Luque, F. J.; Castro, A.; Medina, M.; Martínez, A. (Bioorg. Med. Chem., 2005)

(untitled) - Muñoz-Ruiz, P.; Rubio, L.; García-Palomero, E.; Dorronsoro, I.; del Monte-Millán, M.; Valenzuela, R.; Usán, P.; de Austria, C.; Bartolini, M.; Andrisano, V.; Bidon-Chanal, A.; Orozco, M.; et al. (J. Med. Chem., 2005)

(untitled) - Catto, M.; Pisani, L.; Leonetti, F.; Nicolotti, O.; Pesce, P.; Stefanachi, A.; Cellamare, S.; Carotti, A. (Bioorg. Med. Chem., 2013)

(untitled) - Asadipour, A.; Alipour, M.; Jafari, M.; Khoobi, M.; Emami, S.; Nadri, H.; Sakhteman, A.; Moradi, A.; Sheibani, V.; Moghadam, F. H.; Shafiee, A.; Foroumadi, A. (Eur. J. Med. Chem., 2013)

(untitled) - Ghanei-Nasab, S.; Khoobi, M.; Hadizadeh, F.; Marjani, A.; Moradi, A.; Nadri, H.; Emami, S.; Foroumadi, A.; Shafiee, A. (Eur. J. Med. Chem., 2016)

(untitled) - Vafadarnejad, F.; Mahdavi, M.; Karimpour-Razkenari, E.; Edraki, N.; Sameem, B.; Khanavi, M.; Saeedi, M.; Akbarzadeh, T. (Bioorg. Chem., 2018)

(untitled) - Alipour, M.; Khoobi, M.; Foroumadi, A.; Nadri, H.; Moradi, A.; Sakhteman, A.; Ghandi, M.; Shafiee, A. (Bioorg. Med. Chem., 2012)

(untitled) - Lan, J.-S.; Ding, Y.; Liu, Y.; Kang, P.; Hou, J.-W.; Zhang, X.-Y.; Xie, S.-S.; Zhang, T. (Eur. J. Med. Chem., 2017)

(untitled) - Khunnawutmanotham, N.; Chimnoi, N.; Saparpakorn, P.; Techasakul, S. (Bioorg. Chem., 2016)

(untitled) - Dakin, H. D. (J. Biol. Chem., 1929)

(untitled) - Ellman, G. L.; Courtney, K. D.; Andres, V., Jr; Featherstone, R. M. (Biochem. Pharmacol., 1961)

(untitled) - Cheung, J.; Rudolph, M. J.; Burshteyn, F.; Cassidy, M. S.; Gary, E. N.; Love, J.; Franklin, M. C.; Height, J. J. (J. Med. Chem., 2012)

(untitled) - Jones, G.; Willett, P.; Glen, R. C.; Leach, A. R.; Taylor, R. (J. Mol. Biol., 1997)

(untitled) - Shafferman, A.; Kronman, C.; Flashner, Y.; Leitner, M.; Grosfeld, H.; Ordentlich, A.; Gazes, Y.; Cohen, S.; Ariel, N.; Barak, D. (J. Biol. Chem., 1992)

(untitled) - Ordentlich, A.; Barak, D.; Kronman, C.; Flashner, Y.; Leitner, M.; Segall, Y.; Ariel, N.; Cohen, S.; Velan, B.; Shafferman, A. (J. Biol. Chem., 1993)

(untitled) - Sussman, J. L.; Harel, M.; Frolow, F.; Oefner, C.; Goldman, A.; Toker, L.; Silman, I. (Science, 1991)

(untitled) - Johnson, G.; Moore, S. W. (Curr. Pharm. Des., 2006)

(untitled) - Bourne, Y.; Taylor, P.; Radić, Z.; Marchot, P. (EMBO J., 2003)